The effect of smileys as motivational incentives on children's fruit and vegetable choice, consumption and waste: A field experiment in schools in five European countries. (October 2020) - Gwozdz, W.; Reisch, L.; Eiben, G.; Hunsberger, M.; Konstabel, K.; Kovacs, E.; Luszczki, E.; Mazur, A.; Mendl, E.; Saamel, M.; Wolters, M.; ,
Highlights: The smiley stamp increased fruit and vegetable choice, consumption, but also waste. 77% of the children took a portion with the smiley compared to 40% pre-smiley. Noteworthy are the observed relatively large country differences. The effectiveness of an incentive is strongly context-dependent. Abstract: To assess whether smiley stamps work as a motivational incentive to promote fruit and vegetable eating among children, we conducted a field experiment in ten primary schools in five European countries using one control and one treatment school per country. The six-week experiment was split into three two-week phases before, during and after the smiley was implemented. During the smiley phase, the children received a smiley stamp for choosing a portion of fruits or vegetables. We find an increase attributed to the smiley stamp on children's fruit and vegetable choice and consumption, but also waste. Comparing the effects across countries, we observe significant variations in the smiley effect. This study thus demonstrates, in general, that a low-cost, easy-to-implement incentive such as a smiley stamp has the potential to motivate school children to increase their fruit and vegetable consumption; the study simultaneously underscores the high relevance of context for the effects of incentives.